2016
DOI: 10.14257/ajmahs.2016.04.04
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Study on Correlation Between Dual-income Familyand Internet Addiction of Children

Abstract: With advances in information and communication technologies and especially smart technologies, most people can enjoy favor of those technologies. However, as side effects of those technologies, we are facing with various problems. The typical problems are internet addiction, cyber bullying, cyber gambling, infringement of personal information, copyright violation, and hacking, etc. It is responsibility of our society to provide prevention programs and treatment programs for those side effects. Also, as recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In [20], the correlation between children of dual-income family and internet addiction is analyzed. It is shown that, although the internet addiction rate of dual-income families was higher than single-income families, there was no significant correlation.…”
Section: B Previous Workmentioning
confidence: 99%
“…In [20], the correlation between children of dual-income family and internet addiction is analyzed. It is shown that, although the internet addiction rate of dual-income families was higher than single-income families, there was no significant correlation.…”
Section: B Previous Workmentioning
confidence: 99%